1999
DOI: 10.1017/s0022336000032388
|View full text |Cite
|
Sign up to set email alerts
|

A revised chitinozoan classification

Abstract: The successful definition of chitinozoan genera depends primarily on the precision of the criteria used. A standardized morphological terminology based upon details from scanning electron microscope observations of the most representative taxa bearing these characters is therefore proposed. The 143 genera, or subgenera, described so far in the literature are reviewed in order to exclude invalid taxa and obvious junior synonyms. Particular attention is paid to preventing the overlap of generic definitions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…The classification system of Paris et al (1999) is used. The following symbols are adopted for systematic and biometric descriptions: L = total length of vesicle; 1 = length of chamber; ln = length of neck with collarette; D = maximum diameter of vesicle; dcoll = diameter of collarette; ls = length of spines; L/D = total length of vesicle/maximum vesicle diameter; and L/ln = total vesicle length/length of neck; (x) = mean; N = number of specimens; (max) = maximum observed size; (min) = minimum observed size.…”
Section: Chitinozoans (M Ghavidel-syooki)mentioning
confidence: 99%
“…The classification system of Paris et al (1999) is used. The following symbols are adopted for systematic and biometric descriptions: L = total length of vesicle; 1 = length of chamber; ln = length of neck with collarette; D = maximum diameter of vesicle; dcoll = diameter of collarette; ls = length of spines; L/D = total length of vesicle/maximum vesicle diameter; and L/ln = total vesicle length/length of neck; (x) = mean; N = number of specimens; (max) = maximum observed size; (min) = minimum observed size.…”
Section: Chitinozoans (M Ghavidel-syooki)mentioning
confidence: 99%
“…They bring into question the systematic status of the two genera, although to avoid confusion both are presently retained. They also have implications for other morphologically similar chitinozoan taxa and for the cladogram of Paris et al (1999, fig. 10).…”
Section: Llandovery-wenlock Series Boundarymentioning
confidence: 86%
“…67) showed that the genus Margachitina was derived from Linochitina Eisenack and also illustrated small scale phylogenies in species of Ordovician-Devonian Chitinozoa (Paris 1981, figs 62-64). Multivariate statistics and cladistic analysis have recently been used to group morphologically similar chitinozoan taxa together (Paris et al 1999). Factoral analysis of correspondence shows that there is a close morphological similarity between Margachitina and Calpichitina (Paris et al 1999, figs 6-7).…”
Section: Ma R G a C H I T I N A Margaritanamentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion: the specimens described herein are shorter than Spinachitina cervicornis (Eisenack, 1931), of which the holotype is 240μm long. The proposed neotype (Paris et al, 1999), however, has a length of 140μm. The spines of our specimens differ from those of S. cervicornis (Eisenack, 1931): the latter species always has simple spines, whereas our specimens' spines are sometimes multi-rooted and can have a granular ornamentation.…”
Section: Systematic Palaeontology Sectionmentioning
confidence: 99%